Standard of care framework for occupier during pandemic COVID-19 (SOCO): a facilitation for understanding law relating to tourism industry / Mohamad Sahizam Musa ... [et al.] - Musa, Mohamad Sahizam; Md Pauzi, Suria Fadhillah; Abdul Rahman, Shamsinar; Zainal, Mohd Azim; Ismail, Ida Rosnita (2021)
COVID-19 had severely impacted the industries in Malaysia, especially tourism sector. This outbreak has adversely impacted Malaysia's tourism industry. Nevertheless, government is started to re-open various industries with strict adherence to rules and regulations as provided by the government. The main objective of this product is to impart legal knowledge and awareness on tourism industry players on duties and standard of care to be observed in line with SOP provided by the government. The novelty of this product is from the unified legal framework in which it eliminates the difficulty in learning and understanding the laws by integrating the standard of care as enshrined under the law, coupled with latest SOP ordained by the overnment. This unified framework is very useful as a reference for tourism sectors in operating their business in averting future litigation. This framework is easily marketed as it is in the form of e-brochure containing up-to-date legal information on recent issue during this unprecedented event of Covid-19.